2021
DOI: 10.3389/fimmu.2021.617731
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Atopic Diseases During Childhood – Early Exposure Matters

Abstract: Atopic diseases in childhood are a major burden worldwide and there is still a lack of knowledge about treatable causes. In industrialized countries such as Germany, almost every second child is sensitized to at least one common allergen. Recent studies show that although the predisposition to allergies is inherited, the adaptive immune system of neonates and infants follows a developmental trajectory and whether an allergy actually occurs depends also on timing of allergen exposure including diet as well as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 154 publications
0
11
0
1
Order By: Relevance
“…In a population-based study of 5,276 one-year-old infants, children meeting the current definition of “high risk” for allergic disease (family members with a history of any allergic disease) showed an increase in food allergy compared to those with no family history of allergic disease ( 12 ). A possible explanation for this, supplementary to genetic similarity, is the individualized environment each mother provides for the infant during gestation and breastfeeding ( 13 , 14 ). Therefore, a thorough understanding of the underlying mechanisms that mediate maternal influence to develop food allergy in children is critical to developing prevention and treatment strategies for allergic reactions and similar inflammatory diseases ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a population-based study of 5,276 one-year-old infants, children meeting the current definition of “high risk” for allergic disease (family members with a history of any allergic disease) showed an increase in food allergy compared to those with no family history of allergic disease ( 12 ). A possible explanation for this, supplementary to genetic similarity, is the individualized environment each mother provides for the infant during gestation and breastfeeding ( 13 , 14 ). Therefore, a thorough understanding of the underlying mechanisms that mediate maternal influence to develop food allergy in children is critical to developing prevention and treatment strategies for allergic reactions and similar inflammatory diseases ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most students believed that outdoor exposure might be harmful to children in the context of infection susceptibility. This misbelief is particularly important in implementing prophylactic measures against the development of allergic diseases, as frequent exposure to environmental stimuli has been suggested to reduce the risk of developing these disorders [30][31][32]. Therefore, educational materials on the role of microbes in the development of allergic diseases and the clinical implications are critical to improving the knowledge of medical sciences students whose future careers will be involved in providing direct care and formulating healthcare policies for emerging public health concerns in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism remains elusive. Studies using early life animal models have confirmed that many facets of immunity in early life are distinct from that in adults ( 6 8 ). Regarding the type 2 responses in the lung, the reduction in IL-12 together with the increase in IL-4 in neonates favors Th2 differentiation ( 9 ).…”
Section: Introductionmentioning
confidence: 99%